Transformasi Pemerintahan Daerah Kabupaten Batanghari pada Masa Orde Lama Tahun 1957 - Nabila Desmaliya Putri; Fatonah Nurdin; Padhil Hudaya (AHKAM, 2026)
The transformation of regional government during the Old Order era became an important point in the administrative development of Batanghari Regency because it encouraged the formation of a more modern and centralized bureaucratic system. These changes influenced the life of the Batanghari community, particularly in the fields of government, society, culture, education, and the economy. This study aims to analyze the process of regional government transformation and its impact on the life of the Batanghari Regency community during the Old Order era in 1957. This study used a historical qualitative approach through library research combined with field data. Data sources were obtained from books, scholarly journals, articles, historical documents related to the history of Jambi and the development of regional government in 1957, as well as direct information from parties who knew the historical context. The data were analyzed descriptively through the review, grouping, and interpretation of relevant sources. The results show that regional government transformation brought significant changes to the administrative and bureaucratic systems in Batanghari. The government began to implement a more organized pattern of governance, so the position and role of traditional leaders gradually changed. Nevertheless, the Batanghari community continued to maintain Malay customary values and local traditions as the region’s cultural identity. The development of education, economic activities, and government institutions also influenced patterns of daily community life. Thus, regional government transformation during the Old Order era not only affected the political and administrative fields but also brought social and cultural changes to the Batanghari community as part of Jambi Province. This study contributes to the development of regional history and local government administration studies, particularly in understanding the relationship between bureaucratic change and the socio-cultural dynamics of society.